When to Blame Victims for Negligence: Noncooperators Are Deemed Responsible for Their Own Hardship - Pascal Boyer; Eric Chantland; Lou Safra (Evolutionary Psychology)
In four preregistered studies, we tested implications from a cooperation model that explains victim-blaming as a strategic move, as a way for people to avoid the costs of helping victims (who seem to be unpromising cooperation partners) without paying the reputational cost of being seen as ungenerous, reluctant cooperators. An implication of this perspective is that, if an individual is identified as a poor cooperation prospect to start with, people would be likely to blame that individual for his/her own misfortune, notably by suggesting that the victim was negligent. The four studies presented here support this interpretation, as participants attributed more negligence to an accident victim if that victim had been initially described as less prosocial, either because they denied benefits to others or because they created costs for others. These results are consistent with a familiar result, that people blame victims more if they feel (or want to be seen as) more socially distant from that victim. The present studies may offer a simple, cooperation-based account of this and other aspects of victim-blaming.